Oxidative coupling of N-nitrosoanilines with substituted allyl alcohols under rhodium (III) catalysis - Chaudhary, Priyanka (Frontiers in Chemistry, 2024)
Rhodium(III) catalysis has been used for C-H activation of N-nitrosoanilines with substituted allyl alcohols. This method provides an efficient synthesis of the functional N-nitroso ortho β-aryl aldehydes and ketones with low catalyst loading, high functional group tolerance, and superior reactivity of allyl alcohols toward N-nitrosoanilines. We demonstrated that reaction also proceeds through the one-pot synthesis of N-nitrosoaniline, followed by subsequent, C-H activation. The protocol was also feasible with acyrlaldehyde and methyl vinyl ketone which furnished the same oxidative N-nitroso coupling product.